1999
DOI: 10.1007/s004240050917
|View full text |Cite
|
Sign up to set email alerts
|

Migration of transformed renal epithelial cells is regulated by K + channel modulation of actin cytoskeleton and cell volume

Abstract: Migration of transformed renal epithelial (MDCK-F) cells depends on the polarized activity of a Ca2+-sensitive K+ channel (IK channel; Pflügers Arch 432:R87-R93, 1996). This study was aimed at elucidating the functional link between the IK channel and the actin cytoskeleton which is required for cell locomotion. We monitored migration of MDCK-F cells with video microscopy, quantified filamentous actin with phalloidin binding, and measured the intracellular Ca2+ concentration ([Ca2+]i) with the fluorescent dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 34 publications
5
90
1
3
Order By: Relevance
“…KCa3.1 is involved in microglia functions (Khanna et al, 2001; present study), lymphocyte activation (for review, see Jensen et al, 2002;Schlichter and Khanna, 2002), volume regulation in red blood cells and lymphocytes (Brugnara et al, 1996;Khanna et al, 1999), and migration of renal epithelial cells and mast cells (Schwab et al, 1999;Cruse et al, 2006). Because SK channels are not voltage gated, they are well designed to contribute to the resting potential of non-excitable cells, including immune cells (e.g., microglia).…”
Section: Kca31 and Cell Functionsmentioning
confidence: 68%
“…KCa3.1 is involved in microglia functions (Khanna et al, 2001; present study), lymphocyte activation (for review, see Jensen et al, 2002;Schlichter and Khanna, 2002), volume regulation in red blood cells and lymphocytes (Brugnara et al, 1996;Khanna et al, 1999), and migration of renal epithelial cells and mast cells (Schwab et al, 1999;Cruse et al, 2006). Because SK channels are not voltage gated, they are well designed to contribute to the resting potential of non-excitable cells, including immune cells (e.g., microglia).…”
Section: Kca31 and Cell Functionsmentioning
confidence: 68%
“…Cell volume regulation depends on an intact actin cytoskeleton [19], and perturbations of cell volume themselves change the polymerisation of actin filaments. Cell swelling is accompanied by a disintegration of actin filaments, and cell shrinkage is followed by an assembly of actin filaments [20,21]. Cell migration -a process in which a complex and co-ordinated turnover of actin filaments is of central importance [2,22,23] -also relies on cell volume homeostasis.…”
Section: Discussion Rvd and Cell Migrationmentioning
confidence: 99%
“…In previous studies, it was described that the KCa3.1 channel is highly expressed in malignant melanoma cells [19]. Ion fluctuations mediated by the KCa3.1 channel are known to play a fundamental role in cell migration [23,[64][65][66], since inhibition with specific blockers or activation of this ion channel results in impaired cell mobility [23,67]. Interestingly, it was also reported that the KCa3.1 channels are only active at the rear cell pole of migrating cells due to the intracellular Ca 2+ gradient [22].…”
Section: Mia Protein Secretion Is a Ca 2+ -Regulated Process And Is Dmentioning
confidence: 99%